1990
DOI: 10.1007/bf02624206
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and comparison of fibroblast cell lines from the medial collateral and anterior cruciate ligaments of the rabbit

Abstract: We have developed a procedure to explant fibroblasts from the anterior cruciate ligament (ACL) and the medical collateral ligament (MCL) of the rabbit knee, and have optimized conditions for maintaining them in culture. Maximal growth for both ACL and MCL cells was obtained with Dulbecco's modified Eagle's medium supplemented with 15% fetal bovine serum and 250 microM ascorbate. ACL and MCL fibroblasts displayed intrinsic differences in their responses to changes in culture parameters. Specifically, they displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 10 publications
2
40
0
Order By: Relevance
“…ADMEM containing 5% FBS supported significant increases in collagen type I transcript expression for 6 of 8 groups tested versus their DMEM/10% FBS counterparts, attaining as much as a statistically significant 2-fold increase in (i) E > T and (ii) control test groups (p < 0.05, Table 2 fibroblasts in culture [21]; low collagen type 111 expression was therefore considered to be a favorable outcome in this study. The optimal expression by cells in culture with a mitogen followed by TGF-P placed [3] b > T in contention for further study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…ADMEM containing 5% FBS supported significant increases in collagen type I transcript expression for 6 of 8 groups tested versus their DMEM/10% FBS counterparts, attaining as much as a statistically significant 2-fold increase in (i) E > T and (ii) control test groups (p < 0.05, Table 2 fibroblasts in culture [21]; low collagen type 111 expression was therefore considered to be a favorable outcome in this study. The optimal expression by cells in culture with a mitogen followed by TGF-P placed [3] b > T in contention for further study.…”
Section: Discussionmentioning
confidence: 65%
“…The paper provides the first exhaustive screening of relevant biochemical factors alone, in combination and in sequential application to adult human BMSCs that optimally induce ligament fibroblast lineage. The results presented offer guidance to more complex future studies [10,12,21].…”
Section: J E Morivu Et Ui / Journul O F Orthopuerlicmentioning
confidence: 63%
“…Previous authors have reported minimal outgrowth ( G O cells in 6 days) from rabbit ACL explants [ 191 in serum-free media, and previous studies studying ACL explants and growth factors have been conducted in culture conditions of either 10% serum [33], or 0.5% serum [30]. It has been suggested that the addition of a small amount of serum to the explant culture supplies both the competence and the progression activity required to assay individual growth factors for ACL cells [28,30]. Although we attempted to demonstrate cell outgrowth from ACL explants in serum-free media in a pilot study for this experiment, we were unable to do so, and thus elected to supplement the media with 2% serum ~ a condition which may be more similar to that found inside the joint than a serum-free environment.…”
Section: Discussionmentioning
confidence: 99%
“…12,16 Given similar shapes, larger ligaments with similar collagen composition and fibril size would be expected to be stronger than smaller ones. The ratio of T1C and T3C isoforms is one variable that contributes to differences in ligament scarring, healing, 9,11,13,17 and mechanical strength 15,17 among individuals and among different connective tissues (Figure 1).Collagen synthesis and remodeling follow the transcription of T1C and T3C messenger RNA (mRNA) and the conversion of procollagen into collagen fibers. 9,18-20 Extracellular matrix metalloproteinases and their inhibitors help to regulate collagen remodeling and play an important role in determining the composition and mechanical properties of the ACL.…”
mentioning
confidence: 99%